اسلامی اصطلاحاتِ جزیہ اور خراج : ایک تجزیاتی مطالعہ: Islamic Terms of Jiziyyah and Khirāj: An Analytical Study - Hayat, Munazza (FIKR-O NAZAR فکر ونظر, 2023)
This article argues that a Muslim state receives jizyah from dhimmīs in return for full protection of their lives and property. Jizyah is a kind of cash tax that a Muslim state collects from its non-Muslim people in return for its services, i.e., the complete protection of their lives, properties, honour, and civil rights. But if the non-Muslims personally participate in the defense of the state, as is the responsibility of Muslims, then this tax is waived from them. On the contrary, Muslims are not exempted from paying zakāh. Jizyah is levied only on those who can earn. Jizyah is not levied on the poor, women, children, the elderly, the blind, and monks. In Islam, leniency in receiving jizyah has been ordered. Kharāj (tribute) means setting a very reasonable rate of tax keeping in view the production of the conquered land. The dhimmīs do not own their lands, but they are not removed from their lands, and the nature of the occupation may be hereditary, meaning that the occupation may be passed on to their heirs. They can also settle other matters related to this land. The government receives its ownership rights from these lands in the form of a reasonable rate of kharāj. The lands of the conquerors are not distributed among the conquerors but remain in the possession of the government, which collects kharāj from them.